Entre a técnica e a ética : os usos da natureza na cidade do Recife - Souza, Ana Claudia Batista (2018)
In Brazil, urban policies that call for sustainable urban development have been propagated in the context of environmental impact projects that, during the implementation process, use new technologies in the search for a balance between the quality of life of urban populations and the maintenance of resources available in cities. In the city of Recife (Pernambuco), several projects have been proposed with these characteristics. From this perspective, what is the concept of Sustainable Development advocated in these projects? In what way can Socio-environmental Ethics contribute to this debate? How to think about the risks in this context? Thus, this paper aims to analyse, in the light of socio-environmental ethics, the process of building the "Rios da Gente" Project (North and South sections) in Recife and its relations with other projects as a strategy for inserting the capital in the group of Brazilian cities that excel in urban sustainability or that innovate in the promotion of sustainability. Therefore, one must: identify and characterize the large public-private projects proposed or implemented in Recife between 2007 and 2017 that have a connection with the “Rios da Gente” Project; verify how the technologies proposed in the “Rios da Gente” may contribute in inserting Recife in the circuit of Smart Cities; and identify the socio-environmental risks and conflicts associated with the use of said technologies. We will work under the perspective of the Hypothetical-Deductive Approach method, and the research procedures include bibliographic research, documentary research, field research (direct observation, photographic registration and semi-structured interviews) and virtual research. The investigation of the data collected was performed over the content analysis proposed by Bardin, and the results partially corroborated with the presented hypothesis. By the end of the research, it is concluded that there is a greater concern around the technical characteristics of the construction work, to the detriment of an ethical discussion that better contextualizes the viability, the impacts and the socio-environmental risks involved in the project construction process. It is also identified that the managers and the people accountable in implementing the project care about the insertion of the city into the group of cities that are environmentally sustainable and attractive; while the concern of the population refers on the minimization of the importance of popular participation and the lack of communication about the risks inherent in its implementation.